Success Factors Analysis in Sorong-Manokwari Railway Infrastructure's Project Evaluation with Fuzzy AHP Method - Kambuaya, Flora Tresia Wehelmina; Rarasati, Ayomi Dita (Smart City, 2024)
An infrastructure project is a long-term project that has two consequences in the form of uncertainty related to risk and expansive costs. Are infrastructure projects a good long-run stimulus to growth economy? Particularly for new developing areas like Papua island where project preparation evaluation has to be established in order to implement the project. Railway infrastructure is a project initiated in 2018 by Indonesia President and is currently still under administration processing. As a new incubator project, the first train project in Papua Land contains several factors that may be essential to drive project success. The critical success factors as key factors in the preparation of railway infrastructure projects are seen as the main drivers for the success or failure in said project. This research aimed to find answers by problem formulation through the Analytic Hierarchy Process (AHP) technique, which applies triangular fuzzy number known as Fuzzy AHP. The technique obtained weighting criteria on for 82 indicators that were further identified to result in 27 critical success factors. Ten experts in relevant professions and structural positions in various government institutions were interviewed for the purpose of this research. The evaluation of project preparation carried out here is mainly focused on the project system approach in terms of management and party support as well as key factors for the success of the railway project.